2017
DOI: 10.1371/journal.pone.0176064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of moderate-to-severe thyroid associated ophthalmopathy in 354 Chinese cases

Abstract: Thyroid associated ophthalmopathy (TAO) is an autoimmune inflammatory disorder which disfigures appearance, threatens vision, and results in a pronounced loss of quality of life. The diversity and ethnic difference of the disease manifestations have made it difficult to tailor therapies for each patient. Few studies have analyzed its characteristics in Chinese populations. We therefore enrolled 354 patients with moderate-to-severe TAO from February 2015 to July 2016. A single ophthalmologist consistently perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
35
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 53 publications
(71 reference statements)
7
35
2
Order By: Relevance
“…Because it is a radiotherapy treatment method and has a relevant higher price, there is a trend towards more serious disease status in the cohort. According to a study concerning the clinical characteristics of moderate-to-severe GO in Chinese patients which included 354 patients [ 23 ], 52.26% were female patients, which was similar to our study. The underline reasons may be due to that, firstly, the female-to-male ratio decreases correspondingly with the severity of the disease [ 24 ], and secondly, the predominance of females over males in the incidence of GO was considerably less in Asian patients [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because it is a radiotherapy treatment method and has a relevant higher price, there is a trend towards more serious disease status in the cohort. According to a study concerning the clinical characteristics of moderate-to-severe GO in Chinese patients which included 354 patients [ 23 ], 52.26% were female patients, which was similar to our study. The underline reasons may be due to that, firstly, the female-to-male ratio decreases correspondingly with the severity of the disease [ 24 ], and secondly, the predominance of females over males in the incidence of GO was considerably less in Asian patients [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…The underline reasons may be due to that, firstly, the female-to-male ratio decreases correspondingly with the severity of the disease [ 24 ], and secondly, the predominance of females over males in the incidence of GO was considerably less in Asian patients [ 25 ]. Thirdly, in China, female patients tend to choose primary and second level hospitals for medical service at the beginning of the illness, while male patients always wait and endure until the disease progressed to an unbearable condition [ 23 ], and they always concentrate in tertiary hospitals like our center. Thus, it was rational to found that our cohorts consists a relatively high proportion of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] It was also much higher than that reported by studies from Southeast Asia (2.3% hypothyroid, 11.5% euthyroid) and China (4.5% hypothyroid, 11.3% euthyroid). [ 4 14 ] In a study from India by Khurana et al ., there were 36.67% patients with euthyroid and none had hypothyroidism. [ 7 ] Since the most patients could not afford an antibody profile, subclinical disease could have been missed since antibodies can be positive in the presence of normal thyroid status.…”
Section: Discussionmentioning
confidence: 99%
“…These findings collectively suggest that coexistence of TAO and OMG may follow a distinct pathogenic process rather than an overlapping process of TAO and OMG. Notably, a growing evidence supports the concept that the male TAO patients are more prone to develop active and severe clinical symptoms than the female patients [12]. Previous studies also unveiled a gender bias in co-occurrence of thyroid disease and MG, suggesting that the prevalence in female population was higher than the male population [9,10].…”
Section: Discussionmentioning
confidence: 95%